Malaysia : Financial Sector Assessment Program Banking System Spillovers-Technical Note. (IMF Staff Country Reports; Country Report, 2014)
This Technical Note focuses on banking system spillovers of Malaysia. The note examines the presence of foreign banks and the potential for problems in other jurisdictions to spillover to Malaysia and the overseas operations of Malaysian banks, which make their performance and solvency more exposed to economic and political developments abroad. A key facet of the current crisis is serious problems in advanced economy banks, suggesting a role for spillovers from their claims on Malaysia. Notwithstanding the Asian Financial Crisis, foreign claims of BIS-reporting banks on Malaysia have generally been on an increasing trend since the early 1990s.